Feasibility of Biophysics Flipbook on Respiration System Content for Junior High School Student - Febrian, Andika; Achmad Salehudin; Fairuz Zakirah; Jumadi Jumadi (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
The rapid progress of the era of globalization is pushing for the necessity of the world of education, especially in learning to adapt to applying digital technology. In line with this, the effect of learning is less than optimal during the pandemic, with many problems surrounding media and teaching materials that are not optimal, less attractive, and monotonous, thus making science learning not as effective as it should be. Based on these problems, we need a media that can effectively learn resources based on digital technology in science learning. This study aims to develop a biophysics flipbook product as a medium and teaching material on respiratory system materials for junior high school students. This development research uses a 4D model which consists of define, design, develop, and disseminates—the focus of the discussion in this article only on the feasibility aspect of the product being developed. The research data is the result of the validation score of each aspect which is descriptive quantitative analysis. The results of this research and development resulted in a biophysics flipbook worthy of didactic, construction, technical, and language aspects with very high categories and can be tested or applied in learning at school.